The influence of aesthetic investments on employees. Issue 2 (6th July 2015) - Bjerke, Rune; Ind, Nicholas
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore new constructs related to organizations, art and physical environment. Further, an intention was to explain and discuss whether investments in the physical environment in the form of art, design and architecture do have an effect on employees. Design/methodology/approach – To conclude whether aesthetics had an impact on employees in terms of job satisfaction, motivation and their self-perception of their own ability to provide customer service, the authors undertook a quantitative study of 222 employees in seven companies. The authors subsequently commenced five in-depth, semi-structured interviews with four accessible corporate art buyers and one curator to identify the main motivations for purchasing art and placing it in the work place. Findings – With regard to perceptions of art, design and architecture, the physical environment is perceived as a whole and seems to play a significant role in organizational life for employees in companies that have invested in art. The research implies, however, that the companies that invested in art, design and architecture, despite the positive influence on employees' self-perceived service ability, did not accumulate benefits on service ability relative to employees in companies without art. Practical implications – Managers should cautiously reflect on their motivations for investing in art, design and architecture. Useful motivations might include projecting a desired external image or decoration or expressing connection to a community. Investing in art, design and architecture independent of what the organization is trying to do strategically will create cosmetic solutions that lack any wider purpose. Originality/value – Despite increased corporate interest in aesthetics, little research has been done to determine the effect on employees. The research shortage may be due to the challenge of understanding the meaning of the visible expressions. This paper is a contribution to strengthen the knowledge of the impact of workspace aesthetics on employees (the authors subsequently undertook five in-depth, semi-structured interviews with four accessible corporate art buyers at Storebrand (insurance and banking corporation), Telenor (mobile operator), Hydro (aluminium company), Nordic Choice Hotels and one curator).